2007
DOI: 10.1158/1535-7163.mct-06-0552
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical selection of a novel poly(ADP-ribose) polymerase inhibitor for clinical trial

Abstract: Poly(ADP-ribose) polymerase (PARP)-1 (EC 2.4.2.30) is a nuclear enzyme that promotes the base excision repair of DNA breaks. Inhibition of PARP-1 enhances the efficacy of DNA alkylating agents, topoisomerase I poisons, and ionizing radiation. Our aim was to identify a PARP inhibitor for clinical trial from a panel of 42 potent PARP inhibitors (K i , 1.4 -15.1 nmol/L) based on the quinazolinone, benzimidazole, tricyclic benzimidazole, tricyclic indole, and tricyclic indole-1-one core structures. We evaluated ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
234
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(243 citation statements)
references
References 23 publications
9
234
0
Order By: Relevance
“…studies demonstrated that a variety of PARP inhibitors enhance the antiproliferative and cytotoxic effects of topo I poisons (23)(24)(25)(26)(27)(28)(29)(30)(31). Consistent with those earlier studies, we observed that treating various solid tumor cell lines, including A2780, SKOV3, Ovcar5, and A549 cells, with the PARP inhibitor veliparib (78) sensitized cells to the topo I poison topotecan (Fig.…”
Section: Parp Inhibition Sensitizes Cells To Topo I Poisons-previoussupporting
confidence: 90%
See 1 more Smart Citation
“…studies demonstrated that a variety of PARP inhibitors enhance the antiproliferative and cytotoxic effects of topo I poisons (23)(24)(25)(26)(27)(28)(29)(30)(31). Consistent with those earlier studies, we observed that treating various solid tumor cell lines, including A2780, SKOV3, Ovcar5, and A549 cells, with the PARP inhibitor veliparib (78) sensitized cells to the topo I poison topotecan (Fig.…”
Section: Parp Inhibition Sensitizes Cells To Topo I Poisons-previoussupporting
confidence: 90%
“…A number of previous studies have demonstrated that small molecule PARP inhibitors selectively sensitize cells to topo I poisons in vitro and in vivo (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). At least three explanations have been advanced to explain these observations.…”
mentioning
confidence: 99%
“…Temozolomide (TMZ) is a DNA alkylating agent and is used as a standard-of-care treatment for patients with glioblastoma 13 . Here we used the colorectal cancer cell line SW620 that we knew was sensitive to alkylating agents ( Figure 5a) and which has been used in xenograft studies in combination with TMZ and the PARP inhibitors olaparib or AG014699 14, 15 . First we used the same assay conditions to determine whether increasing concentrations of TMZ induced PAR chains that could be maintained by inhibiting PARG with a potent inhibitor (compound 8 from Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…The PARP inhibitors were found to be potent chemosensitizers, and essentially lack single agent activity. PARP inhibitors under clinical investigation include ABT-888 (developed by Abbott Laboratories, Abbott Park, IL, USA and the USNational Cancer Institute, Bethesda, MD, USA) and AG14361 (developed by Pfizer, Cambridge, MA, USA and the University of Newcastle, Newcastle, UK) (Donawho et al, 2007;Thomas et al, 2007;No authors listed).…”
Section: Telomere Targeting Agentsmentioning
confidence: 99%